Brain stimulation modulates the autonomic nervous system, rating of perceived exertion and performance during maximal exercise - Okano, A. H.; Bodnariuc Fontes, E.; Ayres Montenegro, R.; de Tarso Veras Farinatti, P.; Serpeloni Cyrino, E.; Li, L. M.; Bikson, M.; Noakes, T. D. (British Journal of Sports Medicine, 2015)
Background The temporal and insular cortex (TC, IC) have been associated with autonomic nervous system (ANS) control and the awareness of emotional feelings from the body. Evidence shows that the ANS and rating of perceived exertion (RPE) regulate exercise performance. Non-invasive brain stimulation can modulate the cortical area directly beneath the electrode related to ANS and RPE, but it could also affect subcortical areas by connection within the cortico-cortical neural networks. This study evaluated the effects of transcranial direct current stimulation (tDCS) over the TC on the ANS, RPE and performance during a maximal dynamic exercise.